Microplankton composition, production and upwelling dynamics in Sagres (SW Portugal) during summer 2001 - Loureiro, Sofia (2005)
Microplankton community, production, and respiration were studied alongside physical and chemical conditions at Sagres (SW Portugal) during the upwelling season, from May to September 2001. The sampling station was 5 km east of the upwelling center off Cabo S. Vicente, and 2 km of an offshore installation for bivalve aquaculture.